Lymphatic vessel density is associated with CD8+ T cell infiltration and immunosuppressive factors in human melanoma. (3rd August 2018) - Bordry, Natacha; Broggi, Maria A. S.; de Jonge, Kaat; Schaeuble, Karin; Gannon, Philippe O.; Foukas, Periklis G.; Danenberg, Esther; Romano, Emanuela; Baumgaertner, Petra; Fankhauser, Manuel; Wald, Noémie; Cagnon, Laurène; et al.
ABSTRACT: Increased density of tumor-associated lymphatic vessels correlates with poor patient survival in melanoma and other cancers, yet lymphatic drainage is essential for initiating an immune response. Here we asked whether and how lymphatic vessel density (LVD) correlates with immune cell infiltration in primary tumors and lymph nodes (LNs) from patients with cutaneous melanoma. Using immunohistochemistry and quantitative image analysis, we found significant positive correlations between LVD and CD8 + T cell infiltration as well as expression of the immunosuppressive molecules inducible nitric oxide synthase (iNOS) and 2, 3-dioxygénase (IDO). Interestingly, similar associations were seen in tumor-free LNs adjacent to metastatic ones, indicating loco-regional effects of tumors. Our data suggest that lymphatic vessels play multiple roles at tumor sites and LNs, promoting both T cell infiltration and adaptive immunosuppressive mechanisms. Lymph vessel associated T cell infiltration may increase immunotherapy success rates provided that the treatment overcomes adaptive immune resistance.